Designing Household Survey Questionnaires for Developing Countries - Grosh, Margaret; Glewwe, Paul (Washington, DC: World Bank, 2016)
The objective of this book is to provide detailed advice on how to design multi-topic household surveys based on the experience of past household surveys. The book will help identify define objectives, identify data needed to analyze objectives, and draft questionnaires to collect such data. Much of the book is based on the experience of the World Bank's Living Standard's Measurement Study (LSMS) program, established in 1980 to explore ways the accuracy, timeliness, and policy relevance of household survey data collected in developing countries. It is part of an attempt to extend the range of policy issues that can be analyzed with LSMS data; to increase the reliability and accuracy of the surveys; and to make it easier to implement LSMS surveys. The books first discuss the "big picture" concerning the overall design of surveys, modules to be used, and procedures for combining modules into questionnaires and questionnaires into surveys. Individual modules are discussed in depth as well as major policy issues. The process of manipulating modules to form a better 'fit' in the case of a specific survey is examined. Specific modules include: consumption, education, health employment, anthropometry, non-labor income, housing, price data, environmental issues, fertility, household income, savings, household enterprises, and time use. The third volume provides draft questionnaires, referenced in the prior chapters.